Strategic planning and management for library managers - Matthews, Joseph R.
Libraries enter into strategic planning by a variety of routes, from dynamic technology and rising costs to budget cuts and pressure for change. In this book, Joe Matthews guides library managers towards a greater understanding of the role and attendant responsibilities of strategic planning. Academic, public, and special librarians alike will benefit from Matthews' cogent explanations, real-life examples, and time-tested recommendations. In the process, Matthews addresses such intrinsic questions as: Why is it important that I add strategic thinking to my managerial arsenal? How will strategic planning benefit my library, and is there more than one way to go about it? What is the best way of monitoring and updating our strategic plan for maximum effect? In each case, he debunks false impressions, attends to the goal of providing good service, and identifies at least one new way to communicate the library's strategic importance in the lives of its customers. Academic, public, and special librarians alike will benefit from Matthews' cogent explanations, real-life examples, and time-tested recommendations.